Understanding subjective career success: the impact of attributed importance levels, and organizational factors - Santacilia, Anna Steffen (2017)
Recent studies in the academic field of career management have been discussing the complex construct of subjective career success, focusing to a wide extent on the perceived meanings of such. Building on the 5C-project, the purpose of this study was to investigate influential factors of career success, applying one of the first standardized measures developed to assess multidimensionality of subjective career success. For five criteria (positive relations, work-life balance, learning and development, financial merit, and job characteristics) the study examined the effects of individuals’ attributed importance levels on corresponding satisfying levels of achievement, assessing if high levels of importance match with high levels of achievement. In addition, the study tested the moderating effects of perceived investment in employee development (PIED) and perceived supervisor support (PSS). The survey data came from a large sample of employees across occupational fields in Portugal (N = 431). Results showed that for the criterion positive relations the attributed importance level positively predicted a satisfying achievement level. However for the criteria of learning and development and job characteristics a negative relation was observed. Moreover, results showed that for positive relations the association between importance and achievement levels was moderated by PIED and PSS, such that the moderation effect was stronger among employees with higher levels of PIED and PSS, and thus suggesting a reinforcing effect of the organizational factors. Also the study suggested that PIED and PSS positively predict satisfying achievement levels for all criteria, pointing to the critical role of organizational factors. Conclusions were drawn and limitations and implications discussed.